The body and time - Adamczyk, Monika Dorota (Body and society. Sociology of the body in research and theoretical concepts, 2023)
Body and time are frequently used notions. We understand them intuitively, like „“a wrinkle or a page of the calendar”, and we are convinced that there is nothing new that can be said in this regard. This chapter offers a different, new perspective, situating these two phenomena on evident and less evident planes. The considerations presented in this chapter guide a reader through thematical areas, explaining mutual connections between the body and the time in the context of social processes and phenomena such asthe development of the consumer culture and the accompanying “„cult of a young body”, the ageing of the global population, and the development of science and technology. Sections of this chapter are devoted to the description of the most relevant theories depicting both conceptual categories as well as the most significant issues related to their understanding. The concepts of quantitative time, qualitative time, sequencing of events or social time are illustrated with examples relating them to the concept of the body. Such a procedure not only familiarises the reader with the meaning of particular concepts but also indicates permanent mutual connections between these two conceptual categories on an individual and social level.